Regenerative medicine: from the laboratory looking out. Issue 1 (December 2017) - Edwards, Jennifer; Thomas, Richard; Guilliatt, Robert
Abstract Regenerative medicine has a rich and pluralistic history, characterised by a patchwork of innovation and blind alleys. As scientific researchers, our understanding of this hybrid field of regeneration in a historical and cultural context is far from complete, in part due to the range of non-medical contributory disciplines and a fascination with the future directions of research. This paper explores the different definitions of regenerative medicine and highlights issues faced in regenerative medicine research. We argue that a closer relationship between regenerative medicine and the humanities would enable researchers to better understand the historical context, ethical implications and public perception of this rapidly developing field. In many cases, this would be through better awareness of the existing expertise available in humanities research, which is often not visible to those in the laboratory.